Aspirin-triggered Resolvin D1 ameliorates activation of the NLRP3 inflammasome via induction of autophagy in a rat model of neuropathic pain - Wang, Yi-Hao; Tang, Yu-Ru; Gao, Xiao; Zhang, Nan-Nan; Lv, Qing-Qing; Liu, Juan; Li, Yan (Frontiers in Pharmacology, 2023)
Several studies performed thus far indicate that neuroinflammation may be one of the mechanisms underlying the pathogenesis of neuropathic pain (NP). Autophagy, as an adaptive response, has been regarded as an active process of removing the inflammatory stimulus and restoring homeostatic balance. Resolution of inflammation is a biochemical process mediated by the so-called aspirin-triggered specialized proresolving lipid mediators (AT-SPMs), which are thought to exert protective effects in NP. Recent studies have proposed mechanisms in models of inflammatory disorders and showed a relationship between resolution of inflammation and autophagy. This study aimed to validate the functional effects of Aspirin-triggered Resolvin D1 (AT-RvD1) on in vitro and in vivo models of inflammation and to determine their roles in the regulation of autophagy and activation of the Nod-like receptor protein 3 (NLRP3) inflammasome signaling pathway. METHODS: A NP model was established using L5-6 spinal nerve ligation (SNL) and a model of tumor necrosis factor alpha (TNF-α)-stimulated primary microglia was established to evaluate the effect of SPMs. Western blotting was used to detect the level of NLRP3 inflammasomes complexes proteins (NLRP3, ASC, and Caspase-1) and autophagy-related proteins (ATG5, LC3B, and Beclin1). Immunofluorescence staining was used to understand the autophagy process. The behavioral changes in mice were analyzed using the von Frey filament test. RESULTS: Our results showed that AT-SPMs significantly upregulated the activation of autophagy, which was characterized by an increase in the ratio of LC3B-II/I and accumulation of ATG5 and Beclin1. AT-RvD1 showed a dose-dependent decrease in the upregulated threshold of the mechanical pain sensitivity induced by SNL and suppressed the expression of the NLRP3 inflammasome protein and the production of its corresponding downstream proinflammatory factors. Additionally, AT-RvD1 induced the activation of autophagy of the microglia and decreased the expression of the NLRP3 inflammasome protein and the accumulation of proinflammatory factors in TNF-ɑ-challenged microglia. Thus, these results showed that AT-RvD1 may be a potential alternative therapeutic strategy for the prevention or treatment of NP by inhibition of the NLRP3 inflammasome signaling pathway by targeting the induction of autophagy.